PENILAIAN TINGKAT TEKNOLOGI GALANGAN KAPAL POLITEKNIK KELAUTAN DAN PERIKANAN BITUNG, SULAWESI UTARA - Yuli Purwanto; Fahriadi Pakaya (Politeknik Kelautan dan Perikanan Bitung, 2022)
Indonesian shipyards are generally dominated by shipyards classified as traditional shipyards. Marine and Fisheries Bitung of Polytechnic dockyard or also known as workshop fishing vessel training is one of the shipyards belonging to the Technical Execution Unit of the Ministry of Maritime Affairs and Fisheries. Currently, the shipyard is only used for repairing fishing vessels with a tonnage of less than 30 GT around the town of Bitung. The shipyard uses a slipway type construction or a pull dock that uses an electric winch. The large number of ship repair requests at Bitung Marine and Fisheries Polytechnic shipyard is the reason for the need to increase the capacity of the shipyard. A technology level assessment should be carried out in order to see to what extent the level of technology which includes components of humanware, technoware, infoware and orgaware meets the needs of ship repair at the shipyard. This research was carried out from June to August 2021 using the case study method and analyzed by calculating the TCC value (technological contribution coefficient) of the technological components of technoware, humanware, infoware and orgaware. The highest contribution value is the infoware component, while the technoware component has the lowest contribution. The marine fisheries Bitung Polytechnic shipyard shows that the value of technological contributions lies in the semi-modern classification. Keywords : technological level, technometric model, shipyard.